Use of biologics in the era of COVID- 19: Where do we stand? (2020)
The novel coronavirus disease 2019 (COVID-19) has been spreading for more than 5 months since the World Health Organization declared the COVID-19 pandemic in March 2020. As of August 26, the pandemic had resulted in 23 million confirmed cases and 810,000 deaths worldwide. As the likelihood of prolonged spread without sudden termination of this situation increases, the topic of infection risk in patients treated with biologics is becoming crucial in the dermatologic field. Therefore, we conducted a PubMed search for articles reporting biologics exposure and reviewed guidelines on biologics use published during this pandemic. Although according to phase 2 and 3 clinical trials the most frequently experienced adverse effects of biologics include upper respiratory tract infection, nasopharyngitis, or both, no significant increase in the risk of infection has been observed in treated groups compared with control groups.1,2 However, in most clinical studies, data on the incidence of lower respiratory tract infection (main pathogenicity of COVID-19) for each drug are insufficient, probably because of lack of investigator interest and low incidence (less than 5%). The risk of COVID-19 infection in dermatologic patients treated with biologics can be assessed, focusing on areas in which COVID-19 has spread rapidly (Table I). Although the control for biologics-treated groups is the general population rather than patients treated without biologics, the proportion of polymerase chain reaction–confirmed cases in the biologics-treated group is low (approximately 0%-1.8%). Given that the proportion of suspected (not confirmed but symptomatic) cases in the biologics-treated group varies by study, with up to 18% suspected cases being reported,3 it is important to distinguish and manage high-risk patients. To properly interpret these data, it is necessary to face the limitations of remarkably low proportions of infected patients in the biologics-treated group, limited adjustment of clinical parameters, and heterogeneity of design between studies.